Core Curriculum for Event Medical Leaders. Issue Volume 34:Issue s1(2019) (May 2019) - Lund, Adam; Munn, Matthew Brendan; Ranse, Jamie; Turris, Sheila
Abstract : Introduction: The literature on mass gatherings has expanded over the last decade. However, no readily accessible curriculum exists to prepare and support event medical leaders. Such a curriculum has the potential to align event medical professionals on improving event safety, standardizing emergency response, and reducing community impacts. Methods: We organized collaborative expert focus groups on the proposed "core curriculum" and "electives." Results: Key features of a mass gathering medical curriculum include operations-focused, evidence-informed, best-known practices offered via low barrier, modular, flexible formats with interactive options, and a multi-national focus. Core content proposed: Background (Definitions, Context, Risk, Legalities) Event Medical Planning - "The Seven Steps" - (1.) Assessment and Environmental Scan - Event Emergency Action Plan, (2.) Human Resources, (3.) Equipment/Supplies, (4.) Infrastructure/Logistics, (5.) Transportation (To, On, From), (6.) Communication (Pre, During, Post), and (7.) Administration/Medical Direction Event After-Action Reporting Case-based Activities Electives mirror Core outline and serve as expanded case-studies of specific event categories. Initially proposed electives include: Concerts/Music Festivals Running Events Cycling Events Multi-Sport Events Obstacle Adventure Courses Staged Wilderness Courses Amateur Games Political Gatherings & Orations Religious Gatherings & Pilgrimages Community Gatherings (e.g., Parades, Fireworks, etc.) Discussion: Complex team learning to standardize real-world approaches has been accomplished in other medical domains (e.g., ACLS, AHLS, ATLS, PALS, etc.). A course for event medicine should not re-teach medical content (i.e. first aid, paramedicine, nursing, medicine); it should make available a commonly understood, systematic approach to planning, execution, and post-event evaluation vis a vis health services at events. A 'train the trainer' model will be required, with business operations support for sustainable course delivery. The author team seeks community feedback at WCDEM 2019 in creating 'the ACLS' of Event Medicine.